PERIPHERAL CEMENTO-OSSIFYING FIBROMA OF THE ANTERIOR MAXILLARY GINGIVA - Koswara, Teja (Journal of Health and Dental Sciences, 2024)
Peripheral cemento-ossifying fibroma (PCOF) is a reactive gingival growth due to trauma or local chronic irritation. It occurs in about 2% of all intraoral lesions or about 9.6% of all gingival lesions. Clinical differential diagnoses of PCOF are Peripheral giant cell granuloma, pyogenic granuloma or epulis granulomatosa, irritation fibroma, and osteoid osteoma. This report describes a case of a 39-year-old female with sessile growth measuring 2x2x1 cm on the anterior maxillary gingiva at 11 and 21 region. Clinical diagnosis was epulis granulomatosa. An excisional biopsy was performed, and a histopathological diagnosis was made of peripheral cemento-ossifying fibroma. PCOF is more common in females in the second decade of life and is usually seen in the anterior Maxilla. Lesions are sessile or polypoid growth with normal overlying surface or reddish—generally less than 2 cm. Radiology examinations are usually within normal limits, but sometimes, there are foci of calcification seen within the lesion, superficial bone erosion, or loss of interdental bone with the treatment with excisional biopsy and curettage for periosteum and periodontal ligament tissue. Also, it is essential to eliminate some irritating factors to prevent recurrence. Recurrence rate is high, about 20% of cases. Clinical features of PCOF were similar to other more common gingival lesions such as epulis or fibroma. Histopathological examination was critical to make a definitive diagnosis. DOI : 10.54052/jhds.v4n2.p171-180